2019
DOI: 10.1111/adb.12777
|View full text |Cite
|
Sign up to set email alerts
|

Heroin delay discounting and impulsivity: Modulation by DRD1 genetic variation

Abstract: Background: Dopamine D1 receptors (encoded by DRD1) are implicated in drug addiction and high-risk behaviors. Delay discounting (DD) procedures measure decisional balance between choosing smaller/sooner rewards vs larger/later rewards.Individuals with higher DD (rapid discounting) are prone to maladaptive behaviors that provide immediate reinforcement (eg, substance use). DRD1 variants have been linked with increased DD (in healthy volunteers) and opioid abuse. This study determined whether four dopaminergic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(74 reference statements)
0
8
0
1
Order By: Relevance
“…Both studies used relatively large samples (>100) of out of treatment heroin users and required a positive urinalysis to participate. Although both Stoltman et al ( 2015 ) and Moses et al ( 2019 ) found increases in delay discounting, imagined withdrawal is arguably different from experienced withdrawal. It is also unclear if the increase in discounting found in Stoltman et al ( 2015 ) and Moses et al ( 2019 ) would generalize to more traditional delay discounting tasks with larger amounts of money and longer delays.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Both studies used relatively large samples (>100) of out of treatment heroin users and required a positive urinalysis to participate. Although both Stoltman et al ( 2015 ) and Moses et al ( 2019 ) found increases in delay discounting, imagined withdrawal is arguably different from experienced withdrawal. It is also unclear if the increase in discounting found in Stoltman et al ( 2015 ) and Moses et al ( 2019 ) would generalize to more traditional delay discounting tasks with larger amounts of money and longer delays.…”
Section: Resultsmentioning
confidence: 94%
“…Although both Stoltman et al ( 2015 ) and Moses et al ( 2019 ) found increases in delay discounting, imagined withdrawal is arguably different from experienced withdrawal. It is also unclear if the increase in discounting found in Stoltman et al ( 2015 ) and Moses et al ( 2019 ) would generalize to more traditional delay discounting tasks with larger amounts of money and longer delays. That is, the large effect found due to hypothetical opioid withdrawal may only be large because the task involved heroin.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, internal environment changes may lead to sequence variation and increase the heterozygosity of STR loci and become a possible mechanism of drug abuse [31,32], namely, increased heterozygosity of some alleles may be a risk factor for susceptibility and recurrence [33], while the homozygous genotype of the gene reduces the risk of addiction [34,35].…”
Section: Discussionmentioning
confidence: 99%